Attack of the tyrannosaurus - Stone, Rex.; Spoor, Mike (New York : Scholastic, 2008)
"Tom and Jamie can't believe their luck when they find a secret entrance to a prehistoric world filled with dinosaurs! The first dinosaur they meet is a friendly wannanosaurus. It eats the fruit from super-stinky ginkgo trees. But soon, Tom and Jamie meet a much less friendly dino: a Tyrannosaurus Rex that would like to eat them!"-- P. [4] of cover.
Accelerated Reader AR
Keywords: Dinosaurs -- Juvenile fiction; Boys -- Juvenile fiction; Best friends -- Juvenile fiction; Tyrannosaurus rex -- Juvenile fiction